Xenotransplantation of human adipose derived mesenchymal stem cells in a rodent model of Huntington's disease: motor and non-motor outcomes. (April 2015) - Hosseini, Mahmoud; Moghadas, Marzieh; Edalatmanesh, Mohammad Amin; Hashemzadeh, Mohammad Reza
<x content-type="archive" xml:space="preserve">Abstract</x> Human mesenchymal stem cells (hMSCs) have been presented as alternative sources of cells to be transplanted into the brain in neurodegenerative disorders. In this regard, the efficacy of hMSCs transplants in reducing motor and non-motor deficits in a quinolinic acid (QA) rat model of Huntington's disease (HD) was tested in the present study. After unilateral lesions in striatum by QA, the isolated and purified hMSCs from liposuction of healthy male donors were transplanted into the damaged striatum of the rats. The cells were stably transfected with a vector containing TurboGFP and JRed to make it possible to trace them after transplantation. Animals were tested by motor and non-motor function tests at different times after the cell transplantation. The hMSCs survived 7 weeks in the brains. An improvement was observed in behavioral tests such as apomophine-induced rotation, hanging wire, and rotarod for the hMSC-treated rats. Anxiety like behaviors were decreased in hMSCs-treated animals when they were examined using open field, elevated plus maze, light and dark box, and novelty suppressed feeding tests. Compared to QA, the hMSCs treatment decreased motor activities. These results confirmed the potential efficacy of hMSCs in treatment of behavioral defects in HD. Generally, the data demonstrated that xenologous transplantation of hMSCs could be considered as an ideal candidate for treatment of neurodegenerative diseases, especially HD.